2002
DOI: 10.1074/jbc.m204860200
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory Complex I (NDH I) from Klebsiella pneumoniae, a Sodium Pump

Abstract: The electrogenic NADH:Q oxidoreductase from the enterobacterium Klebsiella pneumoniae transports Na ؉ ions. The complex was purified with an increase of the specific Na ؉ transport activity from 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 53 publications
(63 reference statements)
4
80
0
Order By: Relevance
“…Over the last years, we accumulated evidence that NDH I from enterobacteria like Klebsiella pneumoniae (Gemperli et al 2002(Gemperli et al , 2003 or E. coli (Steuber et al 2000) translocates Na + rather than protons. Our views have been challenged by the hypothesis that complex I from K. pneumoniae (Bertsova and Bogachev 2004) or E. coli (Stolpe and Friedrich 2004) exclusively acts as a proton pump.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last years, we accumulated evidence that NDH I from enterobacteria like Klebsiella pneumoniae (Gemperli et al 2002(Gemperli et al , 2003 or E. coli (Steuber et al 2000) translocates Na + rather than protons. Our views have been challenged by the hypothesis that complex I from K. pneumoniae (Bertsova and Bogachev 2004) or E. coli (Stolpe and Friedrich 2004) exclusively acts as a proton pump.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Na + translocation was strictly coupled to the oxidation of NADH even in the presence of a chemical Na + gradient which would have favored uptake of Na + by the proteoliposomes (Steuber et al 2000;Gemperli et al 2002Gemperli et al , 2003. Obviously, Na + transport through the NuoL subunit in the holo-NDH I is prevented, most likely by the interaction of NuoL with other components of the complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggested that inverted membrane vesicles from E. coli catalyzed NADH-driven Na 1 uptake, which was prevented by inhibitors of complex I but not by protonophores (22). Complexes I from K. pneumoniae and Y. lipolytica, reconstituted into liposomes, were reported to act as Na 1 pumps with a Na 1 /e stoichiometry of 1 (21,23). These observations were contested by other authors that have shown that complexes I from E. coli and K. pneumoniae pump H 1 (24,25).…”
Section: Na 1 As the Coupling Ionmentioning
confidence: 92%
“…Steuber and coworkers (20,21) proposed that some complexes I use Na 1 instead of the consensual H 1 . Transport of The enzyme is an L-shaped membrane protein, consisting of a peripheral and a membrane arm.…”
Section: Na 1 As the Coupling Ionmentioning
confidence: 99%